Space syntax with logic programming: an application to a modern Estate - Fernandes, Pedro Afonso (2023)
Space syntax is a set of theories and techniques for analysing urban settlements and buildings. Here, we propose a new approach to perform syntactic analyses that requires only the declaration in a computer program of the connections between axial lines or convex spaces using Prolog, a logic programming language concerned with artificial intelligence. With this new tool, we found that the deep tree nature of modern estates can be mitigated with a concentric structure similar to the famous Bororo village. In fact, Portela, a high-rise settlement near Lisbon (Portugal), is structured around a central open space (green park) equipped with noninterchangeable facilities (mall, sports centre and church), which are highly synchronised with the surrounding buildings (towers and blocks). The transpatial relations between housing estates and the central zone are maximised either by a distributive ringy network or by a smart grid of pedestrian paths. The result is a compact and integrated settlement with a strong identity and sense of belonging. Nevertheless, this kind of concentric dual system is potentially unstable, a problem that was minimised by forcing a clear opposition with a popular neighbourhood at Portela's vicinity. With this case study, we show how logic programming is a useful tool to describe the patterns of discrete systems as social knowables due to its declarative nature. In fact, a Prolog program represents a certain amount of knowledge, namely, concerned with the structure of an urban settlement (or building), which could be used to answer queries about the social and economic consequences of certain spatial designs.